Dissecting Organ-Specific Aroma-Active Volatile Profiles in Two Endemic Phoebe Species by Integrated GC-MS Metabolomics - Ming Xu; Yu Chen; Guoming Wang (Metabolites, 2025)
Background: Phoebe zhennan and Phoebe chekiangensis are valuable evergreen trees recognized for their unique aromas and ecological significance, yet the organ-related distribution and functional implications of aroma-active volatiles remain insufficiently characterized. Methods: In this study, we applied an integrated GC-MS-based volatile metabolomics approach combined with a relative odor activity value (rOAV) analysis to comprehensively profile and compare the volatile metabolite landscape in the seeds and leaves of both species. Results: In total, 1666 volatile compounds were putatively identified, of which 540 were inferred as key aroma-active contributors based on the rOAV analysis. A multivariate statistical analysis revealed clear tissue-related separation: the seeds were enriched in sweet, floral, and fruity volatiles, whereas the leaves contained higher levels of green leaf volatiles and terpenoids associated with ecological defense. KEGG pathway enrichment indicated that terpenoid backbone and phenylpropanoid biosynthesis pathways played major roles in shaping these divergent profiles. A Venn diagram analysis further uncovered core and unique volatiles underlying species and tissue specificity. Conclusions: These insights provide an integrated reference for understanding tissue-divergent volatile profiles in Phoebe species and offer a basis for fragrance-oriented selection, ecological trait evaluation, and the sustainable utilization of organ-related metabolic characteristics in breeding and conservation programs.